NURSES’ OCCUPATIONAL STRESS IN EMERGENCY CARE AND ISOLATION WARDS AFTER SECOND AND THIRD WAVE OF COVID-19 - Asmaningrum, Nurfika; Pujiyono, Aldi Rahardian; Nur, Kholid Rosyidi M; Zuhroidah, Ida (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: COVID-19 pandemic caused globally public health crises. The massive spread of COVID-19 cases put nurses under immense stress due to high workload and thus high risk of infection, especially those in Emergency Room (ER) and Isolation Wards (IW). Both units were actively involved in handling COVID-19 as the first screening and treatment were given to COVID-19 patients. Objectives: Analyze the differences in stress among nurses working in emergency room and isolation room in designated hospitals after the second and third waves of the COVID-19 pandemic. Methods: The study was designed as comparative descriptive research, with observational and comparative longitudinal approach. There was a 14-month time periods between T1 and T2. The research samples were 33 nurses who working in emergency room (ER) and 32 nurses’ isolation wards (IW) at two hospitals handling COVID-19. Healthcare Workers' Stress questionnaire was used to assess nurse's stress level. Data analysis was performed using the Mann Whitney U Test. Results: The results indicated there were differences levels of stress among the 65 nurses who worked in the emergency room and isolation ward. On average, those Nurses working in the ER experienced lower stress than IW during first wave. By contrast, those Nurses working in IW experienced lower stress than ER during the third wave. There were significant differences on nurses’ stress scores between the two departments during the second wave (p=0.000) and third wave (p=0.036) of COVID-19 pandemic. Conclusion: This study suggests that nurses need to develop adaptive coping mechanisms to maintain decent nursing care during the COVID-19 pandemic. Attempts to anticipate or resolve the work stress are believed to maintain their performance on par with professional nursing care standards, even during the post-pandemic.